Cloud Gaming: An Antipandemic Case for Restaurants - BOVSH, Liudmyla; LEVYTSKA, Inna; HOPKALO, Larysa; RASULOVA, Alla; KOMPANETS, Kateryna (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The study covers a review and testing of solutions for gamification of the restaurant business, which in a pandemic lockdown makes information services attractive to consumers. An architectural composition of gaming client environment of the restaurant was built. A priori probabilities of increasing consumer loyalty to the restaurant entity, which attracts its own server platform, complementing it with cloud gaming, have been determined.